Effect of Laughter Therapy on the Psychological and Physiological State of a Person - Liana Spytska (Psichologija)
The study of laughter therapy can help people better understand how laughter can reduce stress, boost mood, and improve the immune system and overall physical condition, so this topic is quite relevant and necessary in the modern world. The influence of laughter, as a nonverbal emotional component, helps to socialise faster, so studying changes in the psycho-emotional state of a person after laughter therapy is a necessary aspect. The study aims to determine the interaction of the psycho-emotional state and physiological indicators with laughter. The study used the methods of survey, analysis, statistics and generalisation. The dependence of a person’s physical condition and mood before and after positive emotions and laughter was determined. The survey results were also analysed, and the data obtained were summarised. The study summarised the impact of laughter on everyday life and mood. The study also noted that an increase in the level of endorphins in the blood after laughter leads to an improvement in mood and overall well-being. The study analysed and formed a percentage of the main effects of the therapy on people, which included an improvement in mood after laughter 24%, a reduction in stress and an improvement in overall well-being 34%, an increase in energy and life optimism 22%, and an increase in productivity and creativity 20%. The study of laughter and its effects on the body can help in the development of new methods of treating psychological and physiological diseases of the body. Laughter therapy, which is used to improve health through laughter, can have a positive impact on a person’s mental state, reduce stress, improve mood and promote the production of endorphins. Such research could provide a basis for the development of new health and well-being programmes based on the use of humour and laughter to improve both mental and physical health.